Question #2836

simplify each expression by rewriting it as a single logarithm
log X+ log Y+ log Z=
4 ln M + 21n N=
6 log A- 3 log B=
X log A + Y log B- (Z log C + W log D)=

Expert's answer

log X + log Y + log Z = log XYZ

4 ln M + 2 ln N = ln M^{4}N^{2}

6 logA - 3 log B = log A^{6}/B^{3}

X log A + Y log B- (Z log C + W log D)= log A^{X} B^{Y} - log C^{Z} WD = log (A^{X }B^{Y})/(C^{Z}W^{D})

4 ln M + 2 ln N = ln M

6 logA - 3 log B = log A

X log A + Y log B- (Z log C + W log D)= log A

## Comments

## Leave a comment